Combining social information use and comfort seeking for nest site selection in a cavity-nesting raptor. (October 2021) - Morinay, Jennifer; De Pascalis, Federico; Dominoni, Davide M.; Morganti, Michelangelo; Pezzo, Francesco; Pirrello, Simone; Visceglia, Matteo; De Capua, Enrico L.; Cecere, Jacopo G.; Rubolini, Diego
Abstract : When selecting a breeding site, individuals can use social information to reduce the uncertainty regarding habitat quality. Individuals of several bird species tend to reuse nests previously occupied by conspecific or heterospecific competitors but the proximate mechanisms underlying this behaviour remain unclear. Reoccupying nests previously used by competitors could result from individuals copying competitors' choices (the 'social information' hypothesis). Alternatively, it could allow individuals to fulfil their need for a soft nest substrate (e.g. by improving thermal insulation or reducing egg breakage risks) at low costs, regardless of previous occupancy (the 'comfort' hypothesis). Here, we aimed to determine which of these nonmutually exclusive mechanisms triggered the preference for old conspecific nest material in a secondary cavity-nesting raptor that does not add lining material to its nests, the lesser kestrel, Falco naumanni . Using an experimental design forcing settling lesser kestrels to choose between two adjacent nestboxes containing different substrates, we detected a strong preference for soft substrates (peat moss or old conspecific or European roller, Coracias garrulus, nest material) over coarse mineral substrate, especially when the soft substrate also provided social information about previous nest use by a competitor. Despite the apparent absence of preference when directly comparing settlement patterns in soft substrates with and without social information, early settling individuals favoured the substrate with social information, while late settling ones favoured the substrate without social information. This could reflect intraspecific competition avoidance by late arriving individuals that may be competitively inferior to early arriving ones. This hypothesis is supported by a later laying date of young breeders in our population. Our findings suggest that both comfort seeking and social information use explain the preference for previously used nest cavities, and that nest site choices may depend on individual competitive abilities and experience. Highlights: The proximate mechanisms underlying the reuse of old nest material are diverse. Lesser kestrels preferred soft nest substrates, with or without social cues. Between two soft substrates, early breeders favoured the one providing social cues. Late breeders, mostly young, preferred soft substrates with no social cues. Lesser kestrels may adjust social information use according to individual traits.